Working in Groups: Facilitating Positive Group Interactions - Bryan D. Terry (EDIS)
Working together in groups can be a great experience or one filled with stress and anxiety. The goal of facilitating positive group interaction is for every group member to contribute in a more positive and productive manner. This article will review several methods that can facilitate positive group interactions, which will also enhance communication and overall group work. This 3-page fact sheet was written by Bryan D. Terry and published by the UF Department of Family, Youth and Community Sciences, October 2013.